1986
DOI: 10.1104/pp.81.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Fixation via Glutamine Synthetase and Glutamate Synthase in the CAM Plant Cissus quadrangularis L.

Abstract: In a variety of C3 and C4 photosynthetic tissues it is widely recognized that ammonia assimilation proceeds via 9,28,29 To avoid infestation by fungus, the plants were watered twice (0.75 L per tray) with orthocid 50 (3 g captan/L) and also sprayed with the fungicide about 8 weeks prior to use.CO2 and H20 Gas Exchange Measurements. An open gas exchange system (2) was modified to simultaneously measure 3 samples. The CO2 concentration of the measuring gas was adjusted by mixing CO2 free air with CO2 using mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This fact might be explained by relatively high specific activity of GDH under these conditions. The increase of the amount of ammonia as a result of GS inhibition has also been detected by other authors (Stewart and Rhodes, 1976;Berger and Sprengart, 1986). The accumulation of ammonia in relatively high amounts in roots and leaves in the case of 3-hr exposure after infiltration of ammonium sulfate only is apparently caused by relatively low GS activity at this time.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…This fact might be explained by relatively high specific activity of GDH under these conditions. The increase of the amount of ammonia as a result of GS inhibition has also been detected by other authors (Stewart and Rhodes, 1976;Berger and Sprengart, 1986). The accumulation of ammonia in relatively high amounts in roots and leaves in the case of 3-hr exposure after infiltration of ammonium sulfate only is apparently caused by relatively low GS activity at this time.…”
Section: Resultssupporting
confidence: 52%
“…
MSO and azaserine (specific inhibitor of GOGAT) provided L-Methionine sulfoximine (MSO) at concentration 1.25 mM in evidence of the key role of these enzymes in the assimilation vivo causes the inhibition of glutamine synthetase (GS) in both of ammonium in higher plants (Stewart and Rhodes, 1976; roots and leaves of young seedlings of kidney bean following the Berger and Sprengart, 1986). It has been suggested that the accumulation of high levels of ammonia and decrease in amounts role of GDH, which catalyzes the reductive amination reacof free amino acids that is more pronounced in leaves.
…”
mentioning
confidence: 99%
“…However, ammonium ions can also be used as a source of nitrogen by some higher plants in which they are taken up at similar or even at higher rates than nitrate. For many years the assimilation of ammonia in plants was thought to be mediated by the GDH (glutamate dehydrogenase) pathway (Folkes & Yemm, 1958;Singh & Srivastava, 1982;Quetz, Tischner & Lorenzen, 1982;Cammaerts & Jacobs, 1985), but more recently an alternative GS/GOGAT pathway has been established (Lea & Miflin, 1974;Miflin & Lea, 1980;Woo & Osmond, 1982;Berger et al, 1986).…”
Section: Introductionmentioning
confidence: 99%